Study on the degradation law of harmonic gear drive backlash with wear and assembly errors. (October 2022) - Li, Wei; Hao, Lian Jing
Highlights: A more accurate mathematical model of harmonic reducer backlash is established. The sensitivity analysis of different influencing parameters of reducer backlash is carried out. The inner wall of the flexspline is the key position that affects the transmission precision of harmonic reducer. The backlash degradation law of harmonic reducer is investigated. Abstract: Harmonic gear drive mechanism has been widely used in space mechanism, robot and other precision actuators. Based on the theory of probability and statistics, this paper establishes a mathematical model of harmonic gear transmission error considering the assembly and wear among components, and conducts sensitivity analysis and normalization of factors affecting harmonic gear transmission error model. Through Kriging model and Monte Carlo method, reliability degradation law of transmission accuracy is obtained by transmission error function and reliability analysis. Some suggestions are given in the design of harmonic gear drive in the future.